Do rational agents make the same heuristic errors as laymen? Experimental evidence manipulating rationality - Piccoli, Pedro Ribiero; Francisco, Eliane Cristine; Souza, Alceu; Silva, Wesley Vieira da (Revista de Administração da UFSM, 2014)
Prospect Theory revealed that when resorting to certain psychological biases, individuals violate the expected utility in situations involving risk. Later studies replicated the seminal experiment conducted by Kahneman and Tversky (1979), demonstrating that these biases also involve more rational individuals, with the parameters of rationality being set by different proxies such as academic level, knowledge concerning the decision-making process or capital markets experience. The aim of this article was to conduct a deeper analysis of heuristic errors committed by such individuals by directly manipulating the rationality variable for the experimental group, exposing it to the Expected Utility Theory before applying the questionnaire. The results show that there was no significant divergence between the answers given by the experimental group and the control group. Both made the same heuristic errors, corroborating the assumptions of Prospect Theory.